A review of the high-entropy ceramic materials for thermal barrier coatings: Design, synthesis, sintering and properties - Liu Jiahang; Wang Yiyong; Lu Zhe; Zhou Yanwen; Li Yan; Zhang Jing; Lyu Guanlin; Jung Yeon-Gil (Processing and Application of Ceramics)
Thermal barrier coatings are used as a surface technology for hot-end components of turbine engines, and the continuous development of aerospace technology puts higher requirements on ceramic materials for thermal barrier coatings. High-entropy ceramics, as a novel material developed recently, have received wide attention due to their particular structure and high-entropy effect. In recent years, researchers have shown interest in various high-entropy ceramics due to their exceptional thermodynamic properties and outstanding thermal insulation capabilities. These ceramics are being considered for potential application in thermal barrier coatings. This paper reviews the component design theory, synthesis methods, sintering methods and functional performance of high-entropy ceramics for thermal barrier coatings. The future development direction of high-entropy ceramics for thermal barrier coatings is also prospected.